Monitoring N : P Ratio and Cd, Cu, Pb, and Zn Contents in Different Types of Anaerobic Digestates: A Six-Year Study Case - Christina-Luise Roß; Kerstin Nielsen; Jorita Krieger; Marieke Hoffmann; Karen Sensel-Gunke; Frank Ellmer; Timo Kautz (International Journal of Agronomy)
Depending on the quality of the input substrates, process parameters, and postfermentation treatments, digestates may contain a broad spectrum of potentially toxic elements. We suspected that these contents may vary on a broad scale even under seemingly stable process conditions at the biogas plant. Digestates from four biogas plants were therefore continuously analyzed for their contents of phosphorus, nitrogen, cadmium, copper, lead, and zinc over a period of six years. The input substrates varied between the plants (e.g., cattle and pig slurry and rye and maize silage), but were the same for each plant over the whole period. The N : P ratio of the digestates ranged from 2 to 24, with the digestate coming from cofermentation of pig slurry and energy crops (“DG Pig”) having the widest range of N : P ratio over the years. Heavy metal loads of all digestates and during all evaluations did not exceed the limits set by European or German legislation, but as previously expected, showed a large variability especially if cattle or pig manure were used as substrates. Copper content of Cattle slurry before digestion was 897.7 mg kg−1 DM in one case, and zinc content of DG Pig reached 590.2 mg kg−1 DM also once during the investigation. As a result, we strongly recommend to monitor especially phosphorus, copper, and zinc contents in digestates very closely and in short intervals.